Analysis of Operational Performance of Crude Oil Refining and Petrochemical Jetties in Nigeria - Donatus. E. ONWUEGBUCHUNAM; Moses. O. APONJOLOSUN; Sodiq. O. BUHARI; Dotun OJO (Journal of Eta Maritime Science, 2020)
This paper assessed the performance of jetty operations inWarriRefiningandPetrochemical Company (WRPC). Primary data for the study consisted of ship turn round times, volume of cargo and number of vessels handled at the jetties for years 2004 to 2018. These variables served as key performance assessment criteria. In addition, copies of questionnaires on postulated factors affecting terminal performance were administered to a random sample of WRPC staff. Our findings showed that the jetties were being operated at less than optimum level. Trend analysis of the key performance indicators showed existence of continuous decline in operational performance of WRPC over the years covered in the study. Significant factors accounting for this performance outcome were found to include: inadequate berthing facilities, shortage of manpower supply, pipeline vandalisation, inadequate maintenance of jetty facilities and poor documentation process. The study recommended deployment of trained workforce to jetty operations, maintenance of berthing facilities, adequate funding and improved documentation of processes during jetty operations.